2018
DOI: 10.1002/ghg.1808
|View full text |Cite
|
Sign up to set email alerts
|

Potential evaluation of CO2 EOR and storage in oilfields of the Pearl River Mouth Basin, northern South China Sea

Abstract: The Pearl River Mouth Basin (PRMB) is the largest petroliferous sedimentary basin in the northern South China Sea. It is near the coastal economic zone of Guangdong province where a large number of CO2 emission sources are located. Carbon dioxide enhanced oil recovery (EOR) represents an opportunity to promote offshore carbon capture, utilization and storage (CCUS) deployment because CO2 flooding offers a method to recover additional oil while simultaneously sequestering anthropogenic CO2. In this paper, a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…These curves and the column of lithofacies were interpreted on the Petrel platform except for the GR curves (Liu, 2011), and the curves for the #1 well are courtesy of CNOOC Shenzhen. Wood (2006); ** estimated based on method from Mungan (1992); other parameters from Liu (2011) and Li et al (2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These curves and the column of lithofacies were interpreted on the Petrel platform except for the GR curves (Liu, 2011), and the curves for the #1 well are courtesy of CNOOC Shenzhen. Wood (2006); ** estimated based on method from Mungan (1992); other parameters from Liu (2011) and Li et al (2018).…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 shows a list of the reservoir property parameters including rock and fluid properties and engineering information which refer from Li et al (2018) and Liu (2011). In this paper, the reservoir dip (α) was set as a constant value of 3.5° according to actual formation dip in these reservoirs as described in Liu (2011).…”
Section: Reservoir Property Parameter Setmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, preliminary studies on enhanced recovery and CO 2 storage potential in offshore reservoirs have been carried out. Li et al [40] proposed a multi-parameter rapid comprehensive evaluation method for the screening and evaluation of offshore CO 2 flooding potential and evaluated the oil reservoirs in the Pearl River Mouth Basin. Li et al [41] used a multi-parameter dimensionless rapid screening model combined with reservoir composition simulation to evaluate the CO 2 -EOR and CO 2 storage potential of the HZ2-1 Oilfield in the Pearl River Mouth Basin, and concluded that the HZ21-1 Oilfield can implement CO 2 miscible flooding, CO 2 storage potential is 8.1-10.8 Mt.…”
Section: Literature Reviewmentioning
confidence: 99%